Canadian Youth Preferences for E-Cigarettes: A Discrete Choice Experiment - Daniel Eisenkraft Klein; Jiamin Shi; Robert Schwartz (Tobacco Use Insights)
Objectives: The novelty of e-cigarette regulatory policy poses difficulties for evidence-informed decision making because there is little evaluative evidence on the effects of specific policies. One way to provide evidence to inform Canadian policy in this situation is to learn from users how they would behave under different policy scenarios without actually implementing those policies in real-world settings. Discrete Choice Experiments provide an opportunity to undertake this research. Methods: We recruited an online sample of 600 e-cigarette current and past users aged 16-25, using an existing panel of recently recruited e-cigarette users, to participate in a discrete choice experiment. Participants chose their preferred option from a choice of 2 e-cigarette products described by 4 attributes: flavour availability, location availability, nicotine concentration, and price. Results: Our findings provide an overview of how important each attribute (price, nicotine concentration, availability, and flavour) is to young e-cigarette users. Across all features, as price increases, respondents were less willing to purchase. The study provides evidence that while all 4 attributes have strong effects, nicotine concentration and flavour most significantly influenced preferences for e-cigarettes. Conclusion: This could provide points of comparison and a better understanding of how hypothetical regulatory restrictions could prevent youth uptake of e-cigarettes, encourage current youth vapers to quit vaping, and make e-cigarettes available and useful for smokers interested in vaping to help them completely quit combustible cigarette smoking.